Refractory Obstructive Sleep Apnea in a Patient with Diffuse Idiopathic Skeletal Hyperostosis - Ara Darakjian; Ani B. Darakjian; Edward T. Chang; Macario Camacho (Case Reports in Otolaryngology)
Diffuse Idiopathic Skeletal Hyperostosis (DISH) can cause ossification of ligaments and may affect the spine. We report a case of obstructive sleep apnea in a patient with significant upper airway narrowing secondary to cervical DISH. This patient had an initial apnea-hypopnea index (AHI) of 145 events/hour and was treated with uvulopalatopharyngoplasty, genial tubercle advancement, hyoid suspension, septoplasty, inferior turbinoplasties, and radiofrequency ablations to the tongue base which reduced his AHI to 40 events/hour. He redeveloped symptoms, was started on positive airway pressure (PAP) therapy, and later underwent a maxillomandibular advancement which improved his AHI to 16.3 events/hour. A few years later his AHI was 100.4 events/hour. His disease has gradually progressed over time and he was restarted on PAP therapy. Despite PAP titration, years of using PAP therapy, and being 100 percent compliant for the past three months (average daily use of 7.6 hours/night), he has an AHI of 5.1 events/hour and has persistent hypersomnia with an Epworth Sleep Scale questionnaire score of 18/24. At this time he is pending further hypersomnia work-up. DISH patients require prolonged follow-up to monitor the progression of disease, and they may require unconventional measures for adequate treatment of obstructive sleep apnea.